2001
DOI: 10.1210/endo.142.8.8433
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Mouse Ghrelin Gene and Promoter: Occurrence of a Short Noncoding First Exon

Abstract: Ghrelin is a growth hormone-releasing peptide recently discovered in the stomach of rat and human as an endogenous ligand for growth hormone-secretagogue receptor. In the present study, a full-length cDNA for mouse ghrelin has been cloned from the stomach using the oligo-capping and rapid amplification methods, and the organization of its gene and promoter has been analyzed. The mouse ghrelin cDNA was 521 bp long, consisting of 44 bp 5'-noncoding region, 354 bp coding region encoding a pre-proghrelin composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 0 publications
2
34
0
3
Order By: Relevance
“…Sequence analysis was performed on PCR products generated from multiple PIT and HPT cDNA samples. This analysis consistently revealed that, in the HPT and PIT, the dominant ghrelin transcript included In2, where the intron sequence differed from that originally reported by Tanaka et al (2001a; Genbank accession # AB060078) by 2 bp. Specifically, our sequence included eight TG nucleotides repeated in tandem in the middle of the In2 of the mouse ghrelin gene, starting at nucleotide position 1370 (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Sequence analysis was performed on PCR products generated from multiple PIT and HPT cDNA samples. This analysis consistently revealed that, in the HPT and PIT, the dominant ghrelin transcript included In2, where the intron sequence differed from that originally reported by Tanaka et al (2001a; Genbank accession # AB060078) by 2 bp. Specifically, our sequence included eight TG nucleotides repeated in tandem in the middle of the In2 of the mouse ghrelin gene, starting at nucleotide position 1370 (Fig.…”
Section: Resultssupporting
confidence: 70%
“…This ghrelin transcript was composed of a distinct 68-bp sequence at the 5 0 -end, followed by a 252-bp sequence corresponding to exons 4 and 5 of the mouse ghrelin gene (Tanaka et al 2001). Notably, expression of 'full-length' ghrelin mRNA in the mouse testis was not detected in that study, using Northern hybridization.…”
Section: Rodent Datamentioning
confidence: 72%
“…The initial evidence for testicular expression of the ghrelin gene came from a study by Tanaka et al (2001), who identified a testis-specific ghrelin gene derived transcript in the mouse. This ghrelin transcript was composed of a distinct 68-bp sequence at the 5 0 -end, followed by a 252-bp sequence corresponding to exons 4 and 5 of the mouse ghrelin gene (Tanaka et al 2001).…”
Section: Rodent Datamentioning
confidence: 99%
“…DesGln 14 -ghrelin, a splice variant of ghrelin, is the second endogenous ligand for the GHS-R. Only a small percentage of the ghrelin clones isolated from the human stomach library encoded the des-Gln 14 -ghrelin precursor, and the des-Gln 14 -ghrelin peptide was not identified in human stomach. The ratios observed between the two precursor populations, ghrelin and des-Gln 14 -ghrelin, was 5 to 1 in rat stomach, and 6 to 5 in mouse stomach (24). These differences are likely species-specific.…”
Section: Figmentioning
confidence: 85%
“…O. and 0.05% NaN 3 ) containing 0.5% normal rabbit serum. The anti-rat ghrelin-(1-11) or anti-rat ghrelin- (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) antisera were used at final dilutions of 1:6,000,000 and 1:20,000, respectively. After incubation for 12 h, 100 l of 125 I-labeled tracer (15,000 cpm) was added.…”
Section: Methodsmentioning
confidence: 99%